Projeto paisagístico como instrumento de integração de técnicas compensatórias à paisagem urbana: estudo de caso aplicado em planos de infiltração do campus da UFSCar - Pereira, Tássia Romanne Duarte da Silva (2016)
The search for alternative and sustainable solutions for the management of urban stormwater corroborated for the increase of Best Managements Practices (BMPs) use. However, despite this quantitative increase, BMPs have been inserted in the urban context without proper integration with the landscape, whether by legal requirements or by commercial exploration of sustainable urban development. This insertion can create abandoned areas with little or no maintenance, compromising the BMPs functionality and the relationship with the community. The aim of this study was to develop and apply guidelines for the preparation and execution of the landscape design on BMPs targeting their integration into the urban landscape. The guidelines were based on the Low Impact Development, the traditional method of preparation of landscaping design and international recommendations related to BMPs. They were synthesized in seven sequential project steps and applied to two existing infiltration plans in experimental campus watershed of the Universidade Federal de São Carlos - SP. As a result, the guidelines provided a freer design for BMPs, created an identity and multifunctionality, integrating open and green spaces to the hydrologic function.